An Analysis on Domestic Violence (Offence and Punishment) Act of Nepal, 2009 - K. C., Ankita (Kathmandu School of Law Review, 2013)
Women have always been an object of gross and severe violence at the hands of man. The biological weakness of a woman makes her an easy prey to all and sundry. She often is a victim of physical and mental violence not only outside her home but also inside it. Every society accepting the importance of equality of sexes has therefore, made affirmative provisions against gender discrimination. However, in spite of the enactment of these kinds of provisions, equality between men and women continues to be an elusive goal. Hence, women are deprived of basic freedom and thereby are easily exposed to exploitation. This has led violence against women to be a global phenomenon. Violence against women has been gradually recognized to be an important aspect of human rights violation of women. The author this article tries to highlight the concept of violence against women, analyzing the legislative tools available dealing with the violence against women. The author compares the domestic laws dealing on the violence against women with the international tools and draws the attention on the lacunas of domestic laws. The author also recommends what need to be done in future to address the aspect of violence against women in an effective way.